Limited oxygen deficiency in the Arabian Sea during the Miocene - Anya Hess; Alexandra Auderset; Yair Rosenthal; Daniel M Sigman; Alfredo Martínez-García (PANGAEA, 2025)
This dataset contains foraminiferal calcite trace element (I/Ca, Mn/Ca, Mg/Ca, Sr/Ca, Fe/Ca), foraminifera-bound (FB- δ15N) and bulk sediment nitrogen isotope, and lipid biomarker (GDGT) data from sediment core samples at Ocean Drilling Program Sites 730 and 714 in the Arabian Sea. Trace element ratios in foraminiferal calcite serve as proxies for bottom and subsurface oxygenation, and FB-δ15N data are used to reconstruct water column denitrification under extremely low oxygen conditions. GDGT concentrations and Mg/Ca are used to assess Arabian Sea upwelling, and %GDGTRS is used to reconstruct Tethys outflow waters. The data span key intervals of the Miocene, including the Miocene Climate Optimum, and capture long-term variations in Arabian Sea oxygenation in a warmer world. The integrated multi-proxy approach shows the evolution of the Arabian Sea OMZ and its response to climate and oceanographic changes. The data suggest that a persistent OMZ existed since at least the Early Miocene, with further deoxygenation following the MCO, leading to the development of a true oxygen-deficient zone with active denitrification.